2019
DOI: 10.1039/c8fo02300j
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene alleviates AFB1-induced immunosuppression by inhibiting oxidative stress and apoptosis in the spleen of mice

Abstract: Lycopene alleviates AFB1-induced immunosuppression by inhibiting oxidative stress and mitochondria-mediated apoptosis in the spleen of mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 57 publications
3
31
0
Order By: Relevance
“…The spleen can recover and store the iron used to make new red blood cells, which can be quickly replenished and released by the human body in a state of blood loss. The spleen also plays an important role in filtering harmful bacteria in the blood and managing and regulating blood volume (31). Oxidative damage of the skin is a key sign of aging.…”
Section: Discussionmentioning
confidence: 99%
“…The spleen can recover and store the iron used to make new red blood cells, which can be quickly replenished and released by the human body in a state of blood loss. The spleen also plays an important role in filtering harmful bacteria in the blood and managing and regulating blood volume (31). Oxidative damage of the skin is a key sign of aging.…”
Section: Discussionmentioning
confidence: 99%
“…), per hydroxyl radical (HOO − ) and superoxide anion [29,33]. This can result in oxidative stress owing to an imbalance between limited antioxidant defenses and the excessive formation of ROS, resulting in the damage of biological molecules including lipids, proteins, and DNA in cellular systems [34,35]. In support of this hypothesis, several studies have demonstrated the potential for antioxidants to lower the risk of hepatotoxicity caused by exposure to the AF [29,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many studies have reported the pivotal role of oxidative stress induced by AF in eliciting programmed cell death or apoptosis through mitochondrial signaling pathways [25,[40][41][42]. ROS induced mitochondrial damage is known to cause uncoupling of mitochondrial oxidative phosphorylation and the associated reduction in mitochondrial membrane potential following AFB1 administration in vivo and in vitro [25,33,35]. Consequently, mitochondrial alterations cause activation of cytochrome C that modulates Bcl2/Bax gene expression and activate caspase 9 and caspase 3, which results in cell death [41].…”
Section: Discussionmentioning
confidence: 99%
“…Lyc supplementation inhibits LPO during cryopreservation of rabbit sperm (Rosato et al, 2012) and reduces MDA levels in bull sperms (Tvrdá et al, 2016) and mouse spleen (Xu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%